US international lawyers in the interwar years : a forgotten crusade / Hatsue Shinohara. - Shinohara, Hatsue (Cambridge University Press, 2012)
In the interwar years, a group of reform-minded American scholars of international law, such as Quincy Wright and Manley Hudson, challenged traditional international law and strove to establish a 'new' international law in which outlawry of war was institutionalized. They highly valued the Covenant of the League of Nations and the Kellogg-Briand Pact and presented legal arguments in support of them. These scholars were activists in their efforts to promote their views to policy makers and the public. In the US international law community, however, a different group of scholars, notably Edwin Borchard, vehemently opposed the progressive scholars. US International Lawyers in the Interwar Years chronicles those involved in the debate and provides a detailed account of their scholarly works and activities that hitherto have not had the recognition that they deserve.